How does health policy affect practice at a sport mega event? A study of policy, food and drink at Euro 2016. Issue 4 (2nd October 2017) - Piggin, Joe; Tlili, Haifa; Louzada, Bruno Henrique
ABSTRACT: From a public health perspective, there are growing concerns about the commercial arrangements between sports events and companies which sell ultra-processed food and drink. In particular, companies are accused of connecting products that are perceived as unhealthy with sport and physical activity that is perceived as healthy. This study examined the tensions and conflicts between health promotion policy and the marketing and consumption reality at the 2016 European Championship football tournament in France. This study is informed theoretically by a critical, political economy lens. Discourse analysis, semiotic analysis, venue analysis and participant observation were employed to gather data from relevant policy and event management plans, sponsor advertisements, site architecture, food and drink offerings and displays at stadia and fan zones. These sources were assessed for the way they encouraged healthy or unhealthy consumption behaviours. The analysis found that the health advice promoted by the French government and the tournament owners (Union of European Football Associations) differed markedly from the reality at the points of consumption. Unhealthy products dominated inside the stadia and fan zones sampled. In many instances, there were little or no healthy foods on display for customers. Despite a self-proclaimed status as having 'healthy stadia', a limited vision of health at Euro 2016 was promoted, which was largely restricted to the attempted provision of smoke-free spaces. This raises questions for sport mega events which are in receipt of public funding and which claim to promote health. This study encourages policy-makers, sports funders and consumers to critically evaluate health claims made by sport events and sponsors.